Experimental and numerical study of up-down sloshing problems in rectangular tanks - Cruchaga-Ssa., M; Gonzalez-Cofre, O (EMERALD GROUP PUBLISHING LTD, 2026)
PurposeThis paper aims to report an experimental and numerical study of sloshing in rectangular tanks subjected to vertical imposed motion.Design/methodology/approachThe free-surface behavior of a fluid inside a rectangular tank subjected to imposed vertical motion is studied. The experiment consists of imposing motions to a rectangular tank mounted on a shake table controlled for vertical movements. The free surface is measured from images collected with high-speed cameras that record the sloshing experiments performed at different shaking frequencies. The numerical approach uses an algorithm based on the Particle Finite Element Method (PFEM) implemented in an in-house code. The time-periodic regime of the free-surface behavior is specifically studied. The numerical results are validated by comparison with the experimental data.FindingsTo allow a better comparison between experimental and numerical results, the time step used in the simulation should be shorter than that resulting from the sampling frequency of the recordings. To activate the mode shapes, the imposed frequency of the tank motion must be twice the natural frequency.Originality/valueThe novel aspects of this study include the experimental observation of free-surface mode-shapes through controlled vertically imposed motion, as well as the validation of the PFEM for this type of applications. The integration of experimental data, the use of a tailored numerical strategy and the validation of the numerical results constitute the original contributions of this work.